Sistem Informasi Geografis Pemetaan Lokasi Stunting Di Desa Gereneng Timur Berbasis Web - Fathurrahman, Imam; Suhartini, Suhartini; Ahmadi, Hamzan; Fathurrahman, Fathurrahman (Universitas Muhammadiyah Magelang, 2022)
Cases of malnutrition often occur every year, one of them is in Gereneng Timur Village. Because the community's understanding of stunting is still lacking and it is difficult to obtain information quickly, it is a weakness for local governments to be able to identify locations affected by malnutrition. Case handling has also not been effective because data collection is still being carried out manually by the Village Maternity Boarding School (POLINDES) or the village government. The results of this researcher designed web-based software using the waterfall model in the development process and utilized the Geographic Information System (GIS) in mapping stunting locations in East Gereneng Village which aims to display location points along with the number of toddlers affected by stunting and information on how parents prevent stunting from an early age accessed by the community and village government.